- PERAN SUPERVISI –KEPALA SEKOLAH DALAM PENINGKATAN KINERJA GURU SMK SANTO YUSUP – BLITAR - Vincentius Prastowo (Jurnal Manajemen Pendidikan, 2019)
Abstract: The research is aimed at knowing the role of supervision of the principal in the effort of upgrading the performance of the teacher at Vocational Middle School St. Joseph Blitar. The research uses the qualitative approach, with the method of the case study of Robert K. Yin with six steps of the research: plan, design, prepare, collect, analyze, and share. The act of determining the source in this research uses purposive sampling. The technique of gathering data uses three methods: interview, observation and study documentation. The result of the research shows that: first, the carrying out of the diagnosis with regards to the problem of teaching of the teachers at Vocational Middle School St. Joseph Blitar could be seen by (a) gathering data of the performance of the teachers, (b) breaking down into its parts the problem of the performance of the teachers,(c) making the criteria for the conclusion. Second, the improvement of the teaching of the teachers at Vocational Middle School St. Joseph Blitar can be seen from (a) preparing an alternative solution to the problem of the performance of teachers, (b) evaluating the strength and weakness of each of the alternative solution the problem, (c) making the recommendation. Third, formation as a continuous measure to solve the problem of the teaching of the teachers can be seen from (a) applying the decision, (b) monitoring, (c) evaluation of the implementation of the decision. Abstrak: Penelitian ini bertujuan untuk mengetahui peran pengawasan kepala sekolah dalam upaya meningkatkan kinerja guru di SMK St. Joseph - Blitar. Peneliti menggunakan pendekatan kualitatif, dengan metode studi kasus Robert K. Yin dengan enam langkah penelitian yaitu: merencanakan, merancang, mempersiapkan, mengumpulkan, menganalisis, dan berbagi. Tindakan menentukan sumber dalam penelitian ini menggunakan purposive sampling. Teknik pengumpulan data menggunakan tiga metode: wawancara, observasi dan studi dokumentasi. Hasil penelitian menunjukkan bahwa: pertama, pelaksanaan diagnosis masalah pengajaran guru-guru SMK St. Yusup Kota Blitar dapat dilihat dengan adanya proses: (a) mengumpulkan data dari kinerja guru, (b) pemetaan masalah kinerja guru, (c) merumuskan masalah dan penyebab masalah kinerja guru. Kedua, perbaikan permasalahan mengajar guru-guru SMK St. Yusup Blitar dapat dilihat dari: (a) menyiapkan solusi alternatif untuk masalah mengajar guru, (b) mengevaluasi kekuatan dan kelemahan solusi alternative, (c) membuat rekomendasi. Ketiga, langkah pembinaan untuk menyelesaikan masalah mengajar guru dapat dilihat dari: (a) menerapkan keputusan program pembinaan, (b) pemantauan program pembinaan, (c) evaluasi pelaksanaan program pembinaan.